PENGEMBANGAN TUGAS AKHIR MELALUI PROJECT BASED LEARNING MODEL UNTUK MENINGKATKAN GENERIC GREEN SKILLS SISWA - Ana, Ana, Sunarsih; Rohaeni, Neni (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The development of students’ final project through Project-based Learning (PBL)approach was conducted in the workshop of family resource management (FRM) in 7th semester.PBL approach is expected to give contribution to students’ motivation and experience to finish their final assignments of FRM workshop. The objectives of the research are to: (1) develop PBL model for the students’final project; (2) produce learning instruments of PBL such as lesson plans, manual of FRM workshop, and scientific report of FRM workshop. The method of the study was using research and development of Plomp model and quasi experiment for testing the effectiveness of the model. The research subjects were the students from the class of 2009 and 2010 who joined FRM workshop course. The study produced model, lesson plans, and manual of FRM workshop as the outputs. The result showed that project based learning model was effective to improve the students’ generic green skills for project management, collaborative skills, and communicative competence. Keywords: final project, generic green skill, family resource management, Project-Based Learning